EC-SERS detection of thiabendazole in apple juice using activated screen-printed electrodes. (30th March 2023) - Moldovan, Rebeca; Milenko, Karolina; Vereshchagina, Elizaveta; Iacob, Bogdan-Cezar; Schneider, Kenneth; Farcău, Cosmin; Bodoki, Ede
Highlights: Electrochemically roughened AuSPEs are good candidates for SERS substrates. EC-SERS brings many advantages for analytical applications. An electric potential of −0.8 V vs Ag/AgCl enhances the SERS signal of TBZ. TBZ was detected and quantified fast and directly in supplemented juice samples. EC-SERS sensors can be integrated in microfluidic chips for real-time analyses. Abstract: Thiabendazole (TBZ), a benzimidazole fungicide used for post-harvest treatment, may be a trace contaminant of food matrices. In this work, we report the first EC-SERS (electrochemical-surface enhanced Raman spectroscopy) detection of TBZ in spiked apple juice using electrochemically (EC) roughened, gold-based screen-printed electrodes (AuSPEs) and portable instrumentation. Polarizing the substrate (−0.8 V vs Ag/AgCl) improves the recorded SERS signal of TBZ, allowing to reach a limit of detection (LOD) in juice of 0.061 ppm with a relatively wide linear range (0.5–10 μM) and good intermediate precision (%RSD < 10). The recovery of TBZ from unprocessed juice was found to be more than 82 %. Furthermore, a proof-of-concept integration of AuSPEs with a miniaturized flow cell for the preconcentration of TBZ and the controlled delivery of sample and reagents has been demonstrated. This approach paves the way for integrated, portable analytical systems applicable for on-site sample collection, processing, and analysis.